Investigating the variation of intonation contours in Northern Vietnamese tones - Tjuka, Annika; Nguyen, Huong Thi Thu; van de Vijver, Ruben; Spalek, Katharina (Frontiers in Education, 2024)
Intonation is an instrument for structuring discourse and emphasizing different types of information. In German, for example, pitch is used to highlight focus, while in Vietnamese, different pitch contours distinguish lexical tones. As of yet, the interplay between intonation and lexical tone in relation to information structure has not been sufficiently investigated across languages. Vietnamese has six lexical tones and is particularly interesting for investigating the influence of different intonation strategies on the realization of tones. Here, we present a production study with 70 Northern Vietnamese speakers. The participants read six sentences under two conditions. In each sentence, a word occurring in the final position of the sentence and carrying one of the six tones was pronounced in two different discourse contexts. Acoustic analyses of the intonation contours showed that Vietnamese speakers realized the words with significant differences in pitch at the onset. Yet, the strategies for raising or lowering the pitch varied depending on the tone. Our results show the use of prosodic cues in a complex tone system across a large number of speakers. In addition, the study can serve as a starting point for educational programs that include training on intonation patterns in specific contexts.